Fighting erosion in the humid tropics. - Wan Harun, Wan Sulaiman (1988)
Erosion is especially severe in the humid tropics due largely to the high intensity rainfall, erodible soils and human encroachment into steeper topography because of mounting population pressures. Countries in this region can hardly bear the damage caused to the soil resources which hits them twice, once by the loss of productivity upstream and then through flood and sedimentation downstream. While there is much awareness regarding the roots of the problem and consequences thereof, efforts to reduce erosion in the region still leave much to be desired. On the other hand, a large body knowledge and expertise already exists in the field of soil conservation. This paper presents a perspective of the erosion problems in the humid tropics, dwells on some of the conservation programmes instituted and considers new strategies of combating the problem with particular reference to the Malaysian experience. Finally, the role of soil physics research in soil conservation is briefly examined.